2019
DOI: 10.1016/j.pmrj.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydrotherapy on Balance, Functional Mobility, Motor Status, and Quality of Life in Patients with Parkinson Disease: A Systematic Review and Meta‐analysis

Abstract: Background: Individuals with Parkinson disease (PD) present balance and functional mobility disabilities that negatively affect the quality of life (QOL). Objective: To systematically review the effects of hydrotherapy on balance, functional mobility, QOL, and motor status in patients with PD. Design: Systematic review and meta-analysis. Participants: A total of 484 participants were included. The mean age of participants ranged from 54 to 78 years. The average duration of PD ranged from 3 to 10 years. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
2
36
1
4
Order By: Relevance
“…In fact, although there are no SRs that include only RCTs, there have been studies of neck pain 42 and multiple sclerosis. 43 Improvement of symptoms and partial and whole-body functions and symptoms from aquatic exercise are expected to be effective not only for diseases of the musculoskeletal system or connective tissue but also for many other diseases such as those that involve the nervous system 44,45 and circulatory system. 46 A recent SR without MA reported aquatic exercise was effective for improving motor skills in children with cerebral palsy.…”
Section: Current Evidence and Research Challengesmentioning
confidence: 99%
“…In fact, although there are no SRs that include only RCTs, there have been studies of neck pain 42 and multiple sclerosis. 43 Improvement of symptoms and partial and whole-body functions and symptoms from aquatic exercise are expected to be effective not only for diseases of the musculoskeletal system or connective tissue but also for many other diseases such as those that involve the nervous system 44,45 and circulatory system. 46 A recent SR without MA reported aquatic exercise was effective for improving motor skills in children with cerebral palsy.…”
Section: Current Evidence and Research Challengesmentioning
confidence: 99%
“…It should be noted that the Halliwick aquatic intervention group had significantly different MiniBESTest scores at baseline although this was adjusted for in the analyses. Recent systematic reviews have shown that aquatic physiotherapy in PD results in improved balance (as measured by the BBS) when compared to land based physiotherapy [10,45], but it is not clear what elements of aquatic intervention lead to these improvements. Future studies may wish to focus on determining if aquatic physiotherapy broadly results in improvements in balance and fear of falling, or whether specific components of an aquatic program are more effective than others.…”
Section: Plos Onementioning
confidence: 99%
“…It has been proven to be effective for different gait rehabilitation programs, as well as to improve balance and quality of life, and reduce pain and falls. The warm property of water used for hydrotherapy potentially also reduces rigidity [70,71].…”
Section: Hydrotherapymentioning
confidence: 99%
“…In water, innumerable forms of exercises can be performed including warm-up exercises (like jumping and walking), stretching exercises, gait training, cooldown exercises, trunk mobility, balance, coordination and proprioceptive exercises, the Halliwick method, posture exercises, the Ai Chi method, aerobic exercise, the Bad Ragaz method, motor dexterity exercises, and swimming exercises, among others [71].…”
Section: Hydrotherapymentioning
confidence: 99%